Comparative Evaluation of Cytobrush, Whiteside Test and Antimicrobial Sensitivity in Subclinical Endometritis of Repeat Breeding Gir Cows - Nandaniya, Nirbhay R.; Parikh, Suryakant S.; Vala, Karsan B.; Ramoliya, Urvashi B.; Parmar, Devesh J. (Indian Journal of Veterinary Sciences and Biotechnology, 2026)
The present study was undertaken to evaluate the diagnostic efficacy of cytobrush technique and Whiteside test for detection of subclinical endometritis (SCE) in repeat breeding cows, along with bacterial isolation and antimicrobial sensitivity pattern. A total of 98 repeat breeding cows were screened. Cytobrush examination revealed an incidence of 30.61% SCE, whereas Whiteside test detected 24.49% cases. Considering cytobrush as gold standard, Whiteside test showed sensitivity of 80.00% and specificity of 100%. Mean PMN count was significantly higher in SCE affected cows compared to healthy animals. Bacteriological examination revealed Staphylococcus spp. (36.67%) as predominant organism followed by Escherichia coli (26.67%), Streptococcus spp. (16.67%), Corynebacterium spp. (6.67%), and Bacillus spp. (6.67%). Antibiotic sensitivity testing showed maximum sensitivity to ciprofloxacin followed by gentamicin and levofloxacin. The study concluded that cytobrush technique is more reliable diagnostic tool, whereas Whiteside test can be used as field screening method. Antibiotic therapy should be guided by antimicrobial sensitivity testing to ensure effective treatment and minimize resistance.